XMM-Newton view of X-ray overdensities from nearby galaxy clusters: the environmental dependencies - Caglar, Turgay; Hudaverdi, Murat (OXFORD UNIV PRESS, 2017)
In this work, we studied 10 nearby (z <= 0.038) galaxy clusters to understand possible interactions between hot plasma and member galaxies. A multi-band source detection was applied to detect point-like structures within the intra-cluster medium. We examined the spectral properties of a total of 391 X-ray point sources within each cluster's potential well. logN versus log S was studied in the energy range 2-10 keV to measure X-ray overdensities. Optical overdensities were also calculated to solve suppression/triggering phenomena for nearby galaxy clusters. X-ray and optical flux/luminosity properties (X/O, L-X/L-B and L-X/L-K) were investigated for optically identified member galaxies. The X-ray luminosities of our point sources were found to be faint [40.08 <= log (L-X) <= 42.39 erg s(-1 similar to)]. The luminosity range of point sources reveals possible contributions to X-ray emission from low-luminosity active galactic nuclei, X-ray binaries and star formation. We estimated 2 times higher X-ray overdensities from galaxies within galaxy clusters compared to fields. Our results demonstrate that optical overdensities are much higher than X-ray overdensities at a cluster's centre, whereas X-ray overdensities increase through the outskirts of clusters. We conclude that high pressure from a cluster's centre affects the balance of galaxies and they lose a significant amount of their fuel. As a result, the clustering process quenches the X-ray emission of the member galaxies. We also find evidence that the existence of X-ray bright sources within a cluster environment can be explained by two main phenomena: contributions from off-nuclear sources and/or active galactic nucleus (AGN) triggering caused by galaxy interactions rather than AGN fuelling.
Keywords: galaxies: active; galaxies: clusters: general; X-rays: galaxies; X-rays: galaxies: clusters; galaxies: clusters: individual; galaxies: clusters: intracluster medium; ACTIVE GALACTIC NUCLEI; STAR-FORMING GALAXIES; FORMATION HISTORIES; NUMBER COUNTS; RICH CLUSTERS; STELLAR MASS; DEEP FIELD; LUMINOSITY; CHANDRA; EVOLUTION; Astronomy & Astrophysics